Voltage type Γ-source inverters with continuous input current and enhanced voltage boost capability - Loh, Poh Chiang (2013)
Impedance source (Z-source) inverters are introduced recently with numerous advantages over traditional inverters: their voltage/current buck-boost capabilities allow them to be used in various applications; the unique shoot-through feature higher the circuit reliability, elimination of dead-time further improving the output performance. Extending from the basic theory of Z-source inverters, transformer based Z-source (trans-Z-source/trans-quasi-Z-source) inverters are proposed. By making use of magnetic coupled transformers/inductors, these inverters improve the boost capability and they are able to use smaller shoot-through duty ratio compared to conventional Z-source inverters in order to obtain the same voltage boost gain, so that larger modulation index can be utilized. It is preferable for power conversion applications as it lower the dc-link voltage and voltage stress on the switching devices. However, transformer based Z-source inverters have discontinuous input currents so that proper filter might be needed practically in order to protect the voltage source; furthermore, the boost function of trans-Z-source inverter is highly dependent on the transformer designed. To overcome the aforementioned limitations, this paper proposes two new types of Γ-source voltage inverters, which have continuous input current and enhanced voltage boost capability as well as lower requirements for the transformer used. The circuit configuration and theory are verified by both simulations and experiments